The house with a clock in its walls - Bellairs, John (A Lewis Barnavelt mystery, 1993)
Orphaned Lewis Barnavelt comes to live with his Uncle Jonathan and quickly learns that both his uncle and his next-door neighbor are witches on a quest to discover the terrifying clock ticking within the walls of Jonathan's house. Can the three of them save the world from certain destruction?